Copper-containing hydrogenation catalyst for hydrogenolysis of esters
By loading a catalyst of copper and zinc on the alumina carrier and activating CuO by reducing CuO, the problem of insufficient activity and stability of the existing ester hydrogenolysis catalyst is solved, and an ester hydrogenolysis reaction with high efficiency and low by-products is achieved.
Patent Information
- Application Number
- CN202380064640.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-23
- Filing Date
- 2023-06-29
- Publication Date
- 2025-04-18
AI Technical Summary
The existing ester hydrogenolysis catalysts have shortcomings in activity, stability and by-product generation, and it is difficult to meet the needs of high activity, long-term stability and low by-product generation.
The activity and stability of the catalyst are improved by reducing CuO to form Cu(0) microcrystals by using a catalyst loaded with 5-20% by weight of copper and 5-12% by weight of zinc on the alumina support.
The high activity and long-term stability of the ester hydrogenolysis reaction are achieved, the by-product generation is reduced, and the crushing strength and service life of the catalyst are improved.
Smart Images

Figure CN119855647A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to copper-containing hydrogenation catalysts and their use in the hydrogenolysis of esters. Background Art
[0002] The catalytic hydrogenolysis of esters is a commercially important reaction. The hydrogenolysis reaction is:
[0003] RCOOR'+2H2→RCH2OH+R'OH
[0004] Fatty alcohols are useful raw materials, particularly for the production of surfactants and detergents. One process for producing fatty alcohols is by hydrogenolysis of acid methyl esters (FAME), which are typically derived from triglycerides found in animal fats and vegetable oils.
[0005] Hydrogenolysis or hydrogenation of FAME feedstocks using catalysts containing copper and chromium has been described in the prior art, for example in US 2091800. WO 91 / 04789 describes an acid-resistant copper chromite catalyst material containing a promoter metal compound and colloidal silicic acid, a method for its production and use for direct fixed-bed hydration of fatty acids to produce fatty alcohols with appropriate chain lengths. Due to the toxicity of some chromium species, a great deal of research has been conducted on chromium-free catalysts for ester hydrogenolysis.
[0006] JPH1045645A describes a method for producing cyclohexanedimethanol (CHDM) by a two-step process. The first stage involves hydrogenating dialkyl terephthalate in the presence of a precious metal-based nuclear hydrogenation catalyst to produce 1,4-cyclohexanedicarboxylic acid dialkyl esters. The second stage involves hydrogenolysis of 1,4-cyclohexanedicarboxylic acid dialkyl esters in the presence of a copper-zinc-alumina-based catalyst. The preferred catalyst for the second stage comprises 30% to 70% by weight of copper oxide, 20% to 60% by weight of zinc oxide, and 3% to 20% by weight of aluminum oxide in an oxidized form.
[0007] The article "Cu-Zn / Al2O3 Catalyst for the Hydrogenation of Esters to Alcohols" (Chin J Catal, 2010, 31:769-775) describes a catalyst with a copper:zinc:alumina molar ratio of 30:40:30 produced by high-speed collision coprecipitation. After calcination, the catalyst contained approximately 51% copper, 10% zinc and 7% aluminum by weight. The performance of the catalyst was tested in the hydrogenolysis of natural palm oil that had first been transesterified with methanol.
[0008] WO2005 / 070537A1 describes a chromium-free catalyst comprising copper and at least one second metal, which can be obtained by a process involving adding a solution comprising Cu ions and ions of at least one other second metal to an inert support, optionally drying, calcining and reducing at least a portion of the oxidized copper. Examples use silicon dioxide, magnesium oxide, zirconium oxide or titanium dioxide as a support. The catalyst can be used for a variety of purposes, including hydrogenating fatty acids, fatty acid esters, esters and diesters to fatty alcohols, alcohols and diols, respectively.
[0009] WO2016 / 059431A1 describes a catalyst comprising copper, zinc and a silica-alumina material that is not a zeolite. In an example, the catalyst is prepared by precipitating copper nitrate and zinc nitrate using sodium carbonate in the presence of a silica-alumina support. The activity of the catalyst in the hydrogenolysis of methyl laurate is tested.
[0010] WO2016 / 154514A1 describes a catalyst comprising: a mixed metal oxide comprising copper and at least one of manganese, zinc, nickel or cobalt; aluminum oxide; silicon dioxide; and calcium. The catalyst can be used for a variety of applications, including hydrogenolysis of FAME and free fatty acids.
[0011] CN1036576567B describes a method for 2 / g to 400m 2 / g specific surface area and 0.2cm 3 / g to 0.8cm 3 A hydrogenation catalyst comprising 3 to 10 mass % of boron oxide, 6 to 20 mass % of zinc oxide, and 4 to 12 mass % of copper on a gamma alumina carrier having a pore volume of 1.34 g / g. The catalyst can be used for various applications, including the hydrogenation of FAME.
[0012] CN105363454B describes a hydrogenation catalyst comprising: (a) 10 wt % to 50 wt % of copper or its oxide; (b) 0 wt % to 20 wt % of a mixture of ZnO and CdO; (c) ≤5 wt % of a mixture of P2O5 and Bi2O3; and (d) 40 wt % to 70 wt % of a carrier selected from at least one of silica, alumina and molecular sieves, provided that the amount of component (c) is not zero. Comparative catalyst C1 is 10CuO-15ZnO-75Al2O3 and is prepared by co-impregnating an alumina carrier with a solution containing copper nitrate trihydrate and zinc nitrate hexahydrate. The catalyst can be used for a variety of purposes, including the hydrogenation of esters.
[0013] There is a need for further improved ester hydrogenolysis catalysts. Ideally, an ester hydrogenolysis catalyst should satisfy the following properties. First, the catalyst should be highly active for the conversion of the ester substrate. Second, the catalyst should maintain high activity for the conversion of the ester substrate so that the catalyst does not need to be replaced too frequently. Third, the catalyst should be highly selective for the desired ester hydrogenolysis reaction and produce low levels of by-products. Fourth, the catalyst should have a high crush strength and maintain a high crush strength during the reaction. The reason for this is that if the crush strength is too low, the catalyst may disintegrate in the reactor, resulting in an increased pressure drop through the reactor, which may cause blockages and require the catalyst to be discharged prematurely.
[0014] The present invention is a catalyst having a good balance of the above-mentioned properties and a process involving the use of the catalyst in the hydrogenolysis of esters. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is a graph showing the substrate conversion (methyl laurate) versus copper surface area (m 2 / mL cat ) curve graph. Summary of the invention
[0016] The present inventors have now found that a catalyst comprising copper and zinc on an alumina support provides a catalyst having a good balance between high activity for ester hydrogenation, retention of activity, low by-product production and good retention of crush strength.
[0017] In a first aspect, the present invention relates to a process for the hydrogenolysis of an ester substrate, the process comprising the step of carrying out the hydrogenolysis of the ester substrate in the presence of a heterogeneous catalyst, wherein the catalyst comprises:
[0018] 5 wt % to 20 wt % copper on an alumina support; and
[0019] 5 to 12 wt % zinc;
[0020] The total content of elements other than Cu, Zn, Al and O is ≤ 1 wt%.
[0021] The copper content and the zinc content are measured on the oxidation catalyst by the method described in the Examples section. The term "oxidation catalyst" refers to a catalyst in which substantially all of the Zn and Cu are present in the form of oxides. The catalyst used in the method is in reduced form and is preferably prepared by reducing the oxidation catalyst defined in the second aspect of the invention.
[0022] Once installed in the reactor, the oxidation catalyst is typically activated in situ by reducing some or all of the CuO to Cu metal using a feed containing H2. However, ZnO and alumina are not reduced. The activation can be carried out in the gas phase or liquid phase. The result is a catalyst in which some or all of the Cu is present in the form of microcrystalline Cu(0). Such catalysts are referred to herein as "reduced catalysts". An exemplary method for liquid phase activation of a catalyst is described in WO2020 / 053555 (Johnson Matthey Davy Technologies Limited).
[0023] In preferred embodiments, the substrate is an ester of a saturated or unsaturated fatty acid.
[0024] In a second aspect, the present invention relates to an oxidation catalyst for the hydrogenolysis of an ester substrate, wherein the catalyst comprises:
[0025] 5 wt % to 20 wt % copper on an alumina support; and
[0026] 5 to 12 wt % zinc;
[0027] The catalyst has 10m 2 / mL cat Up to 20m 2 / mL cat of copper surface area;
[0028] The total content of elements other than Cu, Zn, Al and O is ≤ 1 wt%.
[0029] The copper content, zinc content and copper surface area were measured on the oxidation catalysts by the methods described in the Examples section.
[0030] In a third aspect, the present invention relates to a method for preparing the oxidation catalyst according to the second aspect, the method comprising the following steps:
[0031] (i) impregnating an alumina support with an impregnation solution comprising copper carbonate and zinc carbonate;
[0032] (ii) drying the product of step (i); and
[0033] (iii) calcining the product of step (ii). DETAILED DESCRIPTION
[0034] Any sub-headings are for convenience only and are not intended to limit the invention.
[0035] Any aspect described as preferred in connection with the catalyst also applies to the catalyst used in the process of the first aspect or prepared by the process of the third aspect.
[0036] catalyst
[0037] The catalyst comprises 5 to 20 wt % copper. The copper loading is lower than many known precipitated copper catalysts. From a cost perspective, low levels of copper are preferred. The preferred copper content is 5 to 12 wt % as this provides a good balance between activity and cost.
[0038] The catalyst comprises 5 to 12 wt % zinc. The addition of zinc not only increases the absolute catalyst activity, but also reduces the decline in catalyst activity over time and reduces the level of by-products produced. High zinc contents (i.e. above 12 wt %), while still providing a more active and selective catalyst than copper catalysts on alumina, result in reduced catalyst activity.
[0039] The total content of elements in the catalyst other than Cu, Zn, Al and O is ≤ 1 wt%. The content of the elements can be determined by inductively coupled plasma mass spectrometry (ICP) or by X-ray fluorescence (XRF).
[0040] Although the contents of copper, zinc and alumina will not be the same between the oxidized and reduced forms of the catalyst, they will be similar in view of the relatively low Cu and Zn contents in the catalysts of the present invention. Therefore, the values for Cu, Zn and "total content of elements other than Cu, Zn, Al and O" apply to both the oxidized and reduced catalysts.
[0041] In a preferred embodiment, the catalyst has 10 m 2 / mL cat Up to 20m 2 / mL cat The copper surface area is measured by the procedure in the Examples section. Although this surface area per unit volume is lower than some known precipitated catalysts, it is higher than many known copper catalysts on alumina supports. Supported alumina catalysts containing copper and zinc with a copper surface area per unit volume in this range are highly active for the hydrogenolysis of esters. In a preferred embodiment, the catalyst has 11 m 2 / mL cat Up to 17m 2 / mL cat of copper surface area.
[0042] Copper and zinc are supported on an alumina support. As used herein, the term "alumina" is not intended to encompass silica-alumina. The silicon content of alumina used herein is ≤ 5 wt%, preferably ≤ 2 wt% (such as ≤ 1 wt%).
[0043] Alumina takes various forms depending on its calcination temperature. The support is preferably α-alumina, γ-alumina or θ-alumina or a mixture thereof. Alumina can be a single form or a mixture of different forms. In a preferred embodiment, the alumina support is γ-alumina.
[0044] Preferably, the catalyst is in the form of particles, spheres or multi-lobed shapes (such as trilobed). Such catalysts can be prepared by impregnating an alumina support in the form of particles, spheres or multi-lobed shapes (such as trilobed). Preferably, the support (and catalyst) is in the form of a trilobed shape.
[0045] Catalyst manufacturing
[0046] The catalysts described herein can be prepared by impregnation of an alumina support. The catalyst can be made by co-impregnation using solutions containing copper and zinc salts or by sequential impregnation (in any order) using a solution containing a copper salt and a separate solution containing a zinc salt. The co-impregnation method is preferred.
[0047] Impregnation techniques are well known to those skilled in the art. Typically, impregnation involves preparing an impregnation solution containing the salt to be impregnated and adding a volume of the impregnation solution to the support, wherein the volume of the impregnation solution is approximately equal to the absorption volume of the support.
[0048] The preferred copper salt is copper carbonate which may be provided for impregnation as a solution of copper carbonate in ammonium hydroxide.
[0049] The preferred zinc salt is zinc carbonate which may be provided for impregnation as a solution of zinc carbonate in ammonium hydroxide.
[0050] It is particularly preferred to provide the copper and zinc salts in the same solution and to apply the metals to the support using a co-impregnation process.
[0051] After the impregnation step (i), the product is dried (step (ii)). If desired, steps (i) and (ii) may be repeated two or more times; this may be desirable if a Cu and Zn loading towards the higher end of the range is desired.
[0052] Once all the desired metals have been impregnated onto the support, a calcination step (step (iii)) is performed. Typical calcination conditions are 200°C to 400°C for 4h±2h. Those skilled in the art can readily determine the calcination conditions, which may vary depending on the scale and equipment used.
[0053] Hydrogenolysis process
[0054] Catalyst as described herein is suitable for hydrogenolysis of ester substrates into corresponding acids and alcohols. Preferred substrates are esters of C6-C22 fatty acids, such as esters of C8-C20 fatty acids. The fatty acid component of the ester can be saturated or unsaturated, and can be straight or branched. The ester is preferably a methyl ester.
[0055] Example
[0056] Analytical procedures
[0057] Tapped bulk density
[0058] About 40 g of catalyst was weighed into a 3 cm diameter graduated cylinder and tapped 2000 times using a vibrating bulk density meter, then the volume of the catalyst was recorded. The density was calculated by dividing the loaded mass by the recorded volume.
[0059] Copper surface area
[0060] The copper surface area was determined using reverse front chromatography as follows: The oxidation catalyst particles were crushed and sieved to a particle size of 0.6 mm to 1.0 mm. About 2.0 g of the crushed material was weighed into a stainless steel tube and heated to 68° C. and purged with helium for 2 minutes. The catalyst was then reduced by heating the catalyst to a maximum of 230° C. at 4° C. / min in a helium stream containing 5% by volume hydrogen and maintaining it at that temperature for 30 minutes until complete reduction. The reduced catalyst was cooled to 68° C. under helium. The reduced catalyst then had 2.5% by volume of N2O in a helium mixture passed over the catalyst. The escaping gas was passed through a gas chromatograph and the N2 evolution was measured.
[0061] Calculate the copper surface area (m2) per gram of catalyst loaded. 2 / g cat ), and then multiplied by the tapped bulk density (g cat / mL) to obtain the copper surface area per mL (m 2 / mL cat ).
[0062] strength
[0063] The crush strength was measured using an Engineering systems CT6 instrument. A crushing speed of 22 mm / min was used with a 50 kg load cell. 20 catalyst particles were analyzed radially and the average was calculated.
[0064] Catalyst Testing Procedures
[0065] 10 mL of catalyst was loaded into a stainless steel reactor based on tapped bulk density in the presence of 45 g of fine (0.1 mm to 0.3 mm) silicon carbide. Silicon carbide was also added above and below the catalyst. The catalyst was activated at 0.6 barg in a 0.5 L / min flow of 5% hydrogen in nitrogen by heating to 240°C at a rate of 1°C / min and holding under these conditions for four hours, then the reactor temperature was reduced to 215°C and the catalyst testing program was started.
[0066] The gas was changed to 100% hydrogen and metered into the apparatus at a rate of 2.8 L / min. Once a reactor pressure of 250 barg was reached, methyl laurate was introduced at a flow rate of 0.375 mL / min. This equated to a H2:ester molar ratio of 82:1 and a 2.25 hr -1 The reactor oil jacket temperature was maintained at 215°C. These conditions were maintained for 168 hours, with online GC analysis completed throughout the process. The flow rates of hydrogen and methyl laurate were then reduced to 1.2 L / min and 0.167 mL / min, respectively, resulting in a 1.0 hr -1 The LHSV of the product was reduced, but the H2:ester ratio was retained. The temperature of the oil jacket was increased and allowed to stabilize at the following temperatures for about 5 hours, with online GC analysis of the product being completed at the following temperatures: 215°C, 220°C, and 225°C.
[0067] The liquid stream was then separated, with all other conditions maintained for about 2 hours to purge the liquid system / catalyst. The reactor was then cooled to room temperature, purged with 5% hydrogen in nitrogen, and then vented under vacuum. The strength of the vented catalyst was analyzed and compared to the fresh strength.
[0068] GC analysis
[0069] On-line GC analysis was completed using a Bruker 456GC to determine the concentrations of the following components:
[0070] Methanol, octene, octane, hexanol, nonane, heptanol, decene, decane, octanal, octyl methyl ether, octanol, 2-nonanone, 2-nonanol, methyl octanoate, octanoic acid, nonanol, dodecene, dodecane, decanal, decyl methyl ether, decanol, 2-undecanone, 2-undecanol, methyl decanoate, decanoic acid, undecanol, tetradecene, tetradecane, dodecanal, dodecyl methyl ether, dodecanol, pentadecane, methyl dodecanoate, dodecanoic acid, C16 wax ether, C16 wax ester, C18 wax ether, C18 wax ester, C20 wax ether, C20 wax ester, C22 wax ether, C22 wax ester, C24 wax ether, C24 wax ester.
[0071] Each component was calibrated using external standards; the response factor for dodecanol was used to estimate any unknown amounts.
[0072] GC parameters
[0073] Column: CP-Sil 8CB 50m 0.32mm 1.2μm
[0074] Syringe: 250℃
[0075] Split 30:1
[0076] Column flow rate 2.0mL / min (constant flow rate)
[0077] Oven: 50℃ for 0.5min, increase to 220℃ at 10℃ / min, increase to 300℃ at 5℃ / min, maintain for 15min
[0078] Detector: 325°C.
[0079] Example 1 (Comparative) - Cu and Zn Precipitated Catalyst (C1)
[0080] C1 was prepared following the procedure described in Example 1 of WO2016 / 059431A1.
[0081] Example 2 (Comparative) - Cu and Zn Precipitated Catalyst (C2)
[0082] C2 is a commercially available precipitation catalyst PRICAT TM CZ 40 / 18T (Johnson Matthey).
[0083] Example 3 (Comparative) - Cu on Alumina Prepared by Impregnation (C3)
[0084] C3 was prepared according to a procedure adapted from WO 99 / 51340 A1.
[0085] An impregnation solution was prepared by dissolving 211.39 g of ammonium carbonate, 253.57 g of basic copper carbonate in 800 mL of ammonium hydroxide. 50 g of a 2.5 mm diameter gamma alumina trilobate was impregnated with this solution until all pores were filled. It was dried at 120°C for four hours before the second impregnation. Once all pores were filled with the impregnation solution, the sample was dried at 120°C for four hours and then calcined at 300°C for four hours. The sample contained 14.5 wt% Cu and 41.1 wt% Al by XRF analysis and had a carbon content of 5.8 m 2 / mL cat of copper surface area.
[0086] Example 4 - Cu and Zn on Alumina Prepared by Impregnation (E4)
[0087] The catalyst was prepared in the same manner as C3 using an impregnation solution consisting of 317.09 g of ammonium carbonate, 194.20 g of basic copper carbonate and 189.47 g of basic zinc carbonate in 1200 mL of ammonium hydroxide. The sample contained 8.5 wt% Cu, 8.4 wt% Zn and 37.6 wt% Al by XRF analysis and had a carbon content of 12.0 m 2 / mL cat of copper surface area.
[0088] Example 5 (Comparative) - Cu and Zn on Alumina Prepared by Impregnation (C5)
[0089] Follow the same procedure as E4 but use KATALCO TM The catalyst was prepared by using 32-4 (3 mm to 4 mm zinc oxide spheres) instead of alumina trilobes. The sample analyzed by XRF contained 7.0 wt% Cu, 60.2 wt% Zn and 1.4 wt% Al and had a carbon content of 8.2 m 2 / mL cat of copper surface area.
[0090] Example 6 - Cu and Zn on Alumina Prepared by Impregnation (E6)
[0091] The catalyst was prepared in the same manner as C3 using an impregnation solution consisting of 52.85 g of ammonium carbonate, 26.54 g of basic copper carbonate and 37.26 g of basic zinc carbonate in 200 mL of ammonium hydroxide. Three impregnations were applied instead of two. The sample analyzed by XRF contained 9.0 wt% Cu, 13.0 wt% Zn and 35.3 wt% Al and had a carbon content of 10.3 m 2 / mL cat of copper surface area.
[0092] Example 7 (Comparative) - Cu and Zn on Silica Prepared by Impregnation (C7)
[0093] The catalyst was prepared in the same manner as C3 but using CARiACT Q-20C (4 mm silica spheres supplied by Fuji Silysia) instead of alumina spheres. The sample contained 8.3 wt% Cu, 8.7 wt% Zn and 34.3 wt% Si by XRF analysis and had a 2.5 m 2 / mL cat of copper surface area.
[0094]
[0095] * The catalyst activity was not measured. The conversion had dropped to 52.1% after 23 hours.
[0096] E4 and E6 show an excellent balance between:
[0097] (1) Hydrogenolysis activity;
[0098] (2) Extended activity, such as the absolute value of conversion after 150 hours and the % conversion at 10 hours
[0099] what is measured;
[0100] (3) the content of by-products, especially when compared to the impregnated catalyst on alumina but without added Zn (C3);
[0101] (4) Good absolute strength and strength retention.
[0102] Example 8 (Comparative) - Cu(C8) on Alumina Prepared by Impregnation with Copper Nitrate
[0103] An impregnation solution was prepared by dissolving 27.9 g of 2.5 hydrated copper nitrate in deionized water to a volume of 26.6 mL. 50 g of 2.5 mm diameter delta / theta alumina trilobes were impregnated with this solution until all pores were filled. It was dried at 120°C for four hours and then calcined at 300°C for four hours. The sample was analyzed by XRF to contain 15.8 wt% Cu and had a carbon content of 4.4 m 2 / mL cat of copper surface area.
[0104] Example 9 (Comparative) - Cu(C9) on Alumina Prepared by Impregnation with Copper Carbonate
[0105] The catalyst was prepared following the same procedure as E4 but using 2.5 mm diameter delta / theta alumina trilobes instead of gamma alumina. The sample contained 17.8 wt% Cu by XRF analysis and had a m 2 / mL cat The Cu loading of C9 is about 13% higher than that of C8, but the Cu surface area is about 23% higher. This shows that using copper carbonate instead of copper nitrate as the impregnation salt can be used to produce catalysts with relatively high copper surface area.
Claims
1. A method for the hydrogenolysis of an ester substrate, the method comprising the step of carrying out the hydrogenolysis of the ester substrate in the presence of a heterogeneous catalyst, wherein the catalyst comprises: 5 wt % to 20 wt % copper on an alumina support; and 5 to 12 wt % zinc; The total content of elements other than Cu, Zn, Al and O is ≤ 1 wt%.
2. The process of claim 1, wherein the catalyst comprises 5 to 12 wt% copper.
3. The method according to claim 1 or claim 2, wherein the alumina support is α-alumina, γ-alumina or θ-alumina or a mixture thereof.
4. The method according to any one of claims 1 to 3, wherein the alumina support is in the form of particles, spheres or multi-lobed shapes.
5. The method according to any one of claims 1 to 4, wherein the alumina support is in the form of a trilobate.
6. The method according to any one of claims 1 to 5, wherein the ester substrate is an ester of a fatty acid.
7. The method according to any one of claims 1 to 6, wherein the ester substrate is an ester of a C6-C22 fatty acid.
8. The method according to any one of claims 1 to 7, wherein the ester substrate is a methyl ester.
9. The process according to any one of claims 1 to 8, wherein the catalyst is prepared by reducing an oxidation catalyst according to any one of claims 10 to 14.
10. An oxidation catalyst for the hydrogenolysis of an ester substrate, wherein the catalyst comprises: 5 wt % to 20 wt % copper on an alumina support; and 5 to 12 wt % zinc; The catalyst has 10m 2 / mL cat Up to 20m 2 / mL cat of copper surface area; and The total content of elements other than Cu, Zn, Al and O is ≤ 1 wt%.
11. The oxidation catalyst of claim 10, wherein the catalyst comprises 5 to 12 wt% copper.
12. The oxidation catalyst according to claim 10 or claim 11, wherein the alumina support is α-alumina, γ-alumina or θ-alumina or a mixture thereof.
13. The oxidation catalyst according to any one of claims 10 to 12, wherein the alumina support is in the form of particles, spheres or multi-lobed shapes.
14. The oxidation catalyst according to any one of claims 10 to 12, wherein the alumina support is in the form of a trilobate.
15. A method for preparing an oxidation catalyst according to any one of claims 10 to 14, the method comprising the following steps: (i) impregnating an alumina support with an impregnation solution comprising copper carbonate and zinc carbonate; (ii) drying the product of step (i); as well as (iii) calcining the product of step (ii).
Citation Information
Patent Citations
Hydrogenation catalyst
CN105363454B
Method of hydrogenating esters
US2091800A
Process for producing acid-resistant catalysts for the direct hydration of carboxylic acids into alcohols
WO1991004789A1
Copper-containing materials
WO1999051340A1
Chromium-free catalysts of metalic CU and at least one second metal
WO2005070537A1